Assessment of students' attitudes towards natural sciences in junior high school - Kurniawan, Dwi Agus; Astalini, Astalini; Nawangsih, Retno (Jurnal Pendidikan dan Pengajaran, 2019)
Assessment of Students' Attitudes towards Natural Sciences in Muaro Jambi District Junior High School. This study aims to determine the attitudes of junior high school students towards natural science subjects with three indicators adopted from TOSRA, namely 1) the normality of science scientists, 2) adoption of scientific attitudes, and 3) pleasure in learning science. The type of research used in this study is a type of survey research using quantitative research designs. This study was conducted in several junior high schools in Muaro Jambi Regency with a sample of 2815 students. The research sample was taken from 2 classes of class VII and VIII using total sampling technique in questionnaire distribution and purposive sampling for interviews. The results of the study of the three indicators show the dominant attitude in the good category. The normality of science scientists is in good category with a percentage of 52%. Adoption of scientific attitudes shows a good category with a percentage of categories 58.4%. The pleasure of learning science is well categorized with a percentage of 65.4%.